Pengaruh S’ Leaf Tea Terhadap Penurunan Kadar Gula Darah Pada Penderita Diabetes Melitus Diwilayah Kerja Puskesmas Cisaat - Sekar Arum Meilasani; Burhanuddin Basri; Amir Hamzah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Diabetes Mellitus is a serious condition that occurs over a long period of time, where blood sugar levels increase due to lack of production of the hormone insulin by the pancreas. Research Objective: To determine the effect of giving S'Leaf Tea on reducing blood sugar levels in diabetes mellitus sufferers in the Cisaat Community Health Center Working Area. Method: research method using Quasi Experimental Pretest-Posttest One Group Design. There were 16 respondents in this study. The results were analyzed using the sample paired T-test. Results: The results of statistical tests using the Paired Samples Test obtained a P value of 0.000 < 0.05, where it can be concluded that there is an effect of S'Leaf Tea on reducing blood sugar levels in diabetes mellitus sufferers at the Cisaat Community Health Center. Conclusion: There is an effect after consuming S'leaf Tea on reducing blood sugar levels in diabetes mellitus sufferers in the Cisaat Community Health Center Working Area. Suggestion: it is hoped that it can be used as an alternative non-pharmacological therapeutic treatment by consuming it.